The Influence of Islamic Social Reporting, Managerial Ownership and Capital Structure on Firm Value - Fitriyani, Endah Nur (UIN Salatiga, 2023)
Increasing competition in the business world makes companies strive to increase the prosperity of shareholders. one of which can be done to increase the prosperity of shareholders by increasing the value of the company. The purpose of this study is to determine the effect of Islamic social reporting, managerial ownership and capital structure on firm value. This study uses secondary data with a population of 30 companies registered on the Jakarta Islamic Index (JII) for the 2016-2020 period. Sampling was carried out using a purposive sampling technique with nine companies that met the criteria in this study. Based on the results of the t (partial) test that the Islamic social reporting variable has a significant positive effect on firm value, the managerial ownership variable has a significant positive effect on firm value, the capital structure variable has an insignificant positive effect on firm value. Keywords: islamic social reporting, managerial ownership, capital structure, firm value